The Case of Doctor-Patient Relationship in Bangladesh: An Application of Relational Model of Autonomy (Bangladesh Journal of Bioethics, 2021)
The objective of this article is to establish an alternative doctor-patient relationship model and describe its importance in the case of the doctor-patient relationship in Bangladesh. There is a lot of diversity in the religious beliefs, social norms and values in Bangladesh. Likewise, the development of biological science as well as medical technology, the allocation of healthcare resources must be considered as an important issue. That is why the autonomy of both doctor and patient is a relational factor here. Besides, the four traditional doctor-patient relationship models offered by Ezekiel J. Emanuel and Linda L. Emanuel are not beyond criticism. So, we need an ideal doctor-patient relationship model for Bangladesh to protect every patient’s autonomy which will give freedom to the patient in choosing their own treatment as well as which will not conflict with the patient’s social or cultural values. In this article, I have selected the relational model of autonomy as the method of alternative doctor-patient relationship model. Hopefully, this alternative model will work better since it considers care first concerning a patient’s autonomy. Besides, doctors would treat their patients as a ‘care seeker’ rather than ‘client’ or ‘customer’, and simultaneously, patients would perceive their physicians as ‘caregivers’. But, applying the relational model of autonomy in the case of doctor-patient relationship is more challenging in Bangladesh due to some obstacles like large numbers of population, illiteracy, insufficiency of skilled doctors and hospitals, corruption in medical sectors, social prejudices and so on. But, if we can overcome these problems, the relational model of autonomy will be considered as a suitable doctor-patient relationship model in Bangladesh.